Microwave-assisted synthesis and single particle spectroscopy of infrared down- and visible up-conversion in Er3+ and Yb3+ co-doped fluoride nanowires. Issue 20 (28th May 2015) - Wawrzynczyk, Dominika; Piatkowski, Dawid; Mackowski, Sebastian; Samoc, Marek; Nyk, Marcin
<x xml:space="preserve">Abstract</x> We report a comprehensive study on the influence of solvent and organic ligands on the up-converted emission of single particles and colloidal solutions of NaYF4 nanowires.